The Franciscan Monastery of the Visitation of the Blessed Virgin Mary in Cetin.: History, Significance, and Efforts to Rediscover Its Location (Povijesni prilozi (Historical Contributions), 2025)
The Franciscan Monastery of the Visitation of the Blessed Virgin Mary in Cetin is best remembered as the site where the Croatian nobility and church prelates assembled on January 1st, 1527. This historic event, documented in a solemn decree, marked the election of Ferdinand I of Habsburg as the Croatian king. Despite its significance, the monastery’s history and importance have received little attention in Croatian historiography. Therefore, the first aim of this paper is to address this gap by utilizing lesser-known and rarely used historical sources. Additionally, the paper seeks to determine the monastery’s location within late medieval Cetin. It examines existing theories about its site, evaluates the validity of these conclusions, and proposes new possibilities for its location based on an analysis of preserved written sources, early modern cartographic data, and field research. The research and considerations presented here indicate that the Franciscan Monastery was most likely founded by Count Stephan III Frankapan in 1463 or 1464, when he brought the Franciscan friars to Cetin and entrusted them with the management of the church of the same name, which had already been a significant pilgrimage site for some time. In the following years, the monastery became extremely important and by the beginning of the 16th century, it served as the center of the Observant Franciscan Vicariate of Bosnia Croatia, which later became a province after the vicariate was elevated to the rank of a province in 1517. By the mid-16th century, they were no longer realistically the Counts Frankapans able to exercise patronage over the Diocese of Krbava or the Franciscan Province of Bosnia Croatia, as the wars with the Ottomans had noticeably diminished their social and material power. The latest possible timeframe for the departure of the Franciscans from Cetin is suggested to be 1575, as mentioned by Adam Baltazar Krčelić. Furthermore, the considerations presented in this paper, which involve a new analysis of known and unknown medieval and early modern written sources and maps, as well as field reconnaissance, provide a conclusive set of indications that the Franciscan Monastery of the Visitation of the Blessed Virgin Mary was most likely located on the plateau on the eastern slope, east of the current road leading from Cetingrad to Podcetin, at the entrance to the village of Podcetin.